Population-based nutrition study on an urban population with type 2 diabetes mellitus - Aleksandr Konstantinovich Kuntsevich; Svetlana Vladimirovna Mustafina; Malyutina Sofya Konstantinovna; Evgeniyi Georgievich Verevkin; Rymar Oksana Dmitrievna (Сахарный диабет)
Aim. The aim of our cross-sectional study was to evaluate the nutrition (or diet) habits of people with type 2 diabetes mellitus (DM) in the urban population (45–69 years) of Novosibirsk.Materials and methods. We included 1,041 people with DM and 8,095 people without DM in this study. The nutrition data were obtained via a population survey using a questionnaire to assess the frequency of food consumption within the framework of HAPIEE, an international project.Results. The prevalence of DM was 11.4% in this study population. The nutrition intake analysis showed that carbohydrate consumption in both men and women with DM was significantly lower compared with that in those without DM, while fat and protein intake were significantly higher. In men with type 2 DM, the proportions of black bread, vegetables, dairy products and meat in the diet were significantly higher, while the proportions of white bread and sweets in the diet were significantly lower compared with their counterparts without DM. Women with DM also had significantly higher proportions of black bread, vegetables, dairy products, meat and fish in the diet and lower proportions of white bread, potatoes and sweets in the diet than the controls. The proportions of fruit, eggs and alcohol intake did not differ between the groups for both men and women. In men, there was also no difference in the proportions of potatoes, vegetables and fish intake between the groups.Conclusion. The diets of both patients with DM and the general population in Novosibirsk are not well balanced.